PORTFOLIO OPTIMIZATION OF COMMERCIAL BANK CREDITS: A LITERATURE REVIEW - Ziyodilloyev, Khushnud (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This paper examines the portfolio optimization of commercial banks' credits, with a focus on the banking sector's efficiency. Following the mortgage bond crisis, banks have become more cautious in allocating financial resources and assessing risks. Evaluating the credit portfolioʻs efficiency and quality is crucial in determining the role of credit operations, effective credit utilization, risk levels, interest rates, loan income, interest margin and overdue loans. The optimal credit portfolio in Uzbekistan’s banking system depends on factors such as economic conditions, risk appetite, regulations, and borrower creditworthiness. In general, an optimal credit portfolio for Uzbekistani banks should be well-diversified, balanced and aligned with the country’s economic development priorities.